Application of multithreading technique for multiple input and multiple output mechatronic system - Saaidon, Nur'Ain; Sediono, Wahju (School of Engineering and Technology Faculty of Art Design and Technology University of Derby, United Kingdom, 2017)
In this paper, multithreading technique is being applied in the system algorithm and evaluated for real-time color marker based navigation system for image guide surgery. This work was carried out to investigate the effect of multithreading technique on the performance of multiple inputs and multiple out system. The purpose of this implementation is to reduce the execution time taken for the image processing algorithms in usual sequential algorithm. It is also to ensure that while the system is executing multiple process of image manipulations, the system navigation unit, robotics arm and the user interface display does not pause any longer than necessary. From the experiment, the graphical user interface for the system with multithreaded algorithm can achieve up to 27 Hz refresh rate and 36.56 msec per cycle with input values being updated in every 10 msec. The result shows that the system is able to track the tool marker and navigate it to the target marker with certain error tolerance. The result also shows that the system has significantly improved the refresh rate of the system’s graphical user interface by applying multithreaded algorithm in the system control code compare to normal sequential single thread algorithm.